Back Cover: Epicocconone–Hemicyanine Hybrids: Near Infrared Fluorophores for Protein Staining and Cell Imaging (Chem. Eur. J. 8/2017). Issue 8 (13th December 2016) - Karuso, Peter; Loa Kum Cheung, Wendy; Peixoto, Philippe A.; Boulangé, Agathe; Franck, Xavier
Abstract : The design, synthesis and characterization of a new family of long Stokes' shift near infrared (NIR) fluorescent dyes obtained by hybridizing epicocconone and hemicyanins are reported. The dyes can be used for protein gel staining and confocal microscopy. For example, one of the compounds labeled specific intracellular organelles in SW480 cancer cells. More information can be found in the Full Paper by P. Karuso, X. Franck et al. onpage 1820 ff.